Mobile Remote Monitoring of Intimate Partner Violence Among Pregnant Patients During the COVID-19 Shelter-In-Place Order: Quality Improvement Pilot Study - Krishnamurti, Tamar; Davis, Alexander L; Quinn, Beth; Castillo, Anabel F; Martin, Kelly L; Simhan, Hyagriv N (JMIR Publications, 2021)
BackgroundIntimate partner violence (IPV) is one of the leading causes of pregnancy-related death. Prenatal health care providers can offer critical screening and support to pregnant people who experience IPV. During the COVID-19 shelter-in-place order, mobile apps may offer such people the opportunity to continue receiving screening and support services. ObjectiveWe aimed to examine cases of IPV that were reported on a prenatal care app before and during the implementation of COVID-19 shelter-in-place mandates. MethodsThe number of patients who underwent voluntary IPV screening and the incidence rate of IPV were determined by using a prenatal care app that was disseminated to patients from a single, large health care system. We compared the IPV screening frequencies and IPV incidence rates of patients who started using the app before the COVID-19 shelter-in-place order, to those of patients who started using the app during the shelter-in-place order. ResultsWe found 552 patients who started using the app within 60 days prior to the enforcement of the shelter-in-place order, and 407 patients who used the app at the start of shelter-in-place enforcement until the order was lifted. The incidence rates of voluntary IPV screening for new app users during the two time periods were similar (before sheltering in place: 252/552, 46%; during sheltering in place: 163/407, 40%). The overall use of the IPV screening tool increased during the shelter-in-place order. A slight, nonsignificant increase in the incidence of physical, sexual, and psychological violence during the shelter-in-place order was found across all app users (P=.56). Notably, none of the patients who screened positively for IPV had mentions of IPV in their medical charts. ConclusionsApp-based screening for IPV is feasible during times when in-person access to health care providers is limited. Our results suggest that the incidence of IPV slightly increased during the shelter-in-place order. App-based screening may also address the needs of those who are unwilling or unable to share their IPV experiences with their health care provider.